Formulation Test of Dracontomelon dao (Blanco) Merr. & Rofe Leaf Extract Powder as an Anti-Diarrheal Escherichia coli Method In Vivo - Dwiyanti, Ratih Dewi; Thuraidah, Anny; Nurlailah, Nurlailah (Medical Laboratory Technology Journal, 2024)
Dracontomelon dao (Blanco) Merr. & Rofe is one of the medicinal plants used in the community. This study aims to analyze the effectiveness of  Dracontomelon dao (Blanco) Merr. & Rofe extract powder as an antidiarrheal against Escherichia coli in vivo. Dracontomelon dao (Blanco) Merr. & Rofe leaf comes from Hulu Sungai Utara, South Kalimantan, Indonesia, and is macerated with 96% ethanol—Dracontomelon dao extract powder (Blanco) Merr. & Rofe is made with three parts thick extract, four parts Lactose, and four parts Starch. Experimental rat were conditioned to develop diarrhea and were treated with extract powder with varying doses per kg of body weight, namely 250 mg, 500 mg, and 750 mg. After treatment on day 6, rat recovered from diarrhea in the 750 mg dose treatment group as much as 78%, while the positive control total recovery on day 6 reached 100%. After treatment on day 6, the number of Escherichia coli colonies in rat feces decreased, namely the lowest in the 750mg dose treatment group, 276 colonies/gr. This research concludes that Dracontomelo dao (Blanco) Merr. & Rofe leaf extract powder is effective as an anti-diarrhea against Escherichia coli in experimental rat. Further research is needed on human test subjects to obtain anti-diarrhea drugs with safer and more effective formulations.